A unified thermo-mechanical model for coal mill operation. (November 2015) - Agrawal, V.; Panigrahi, B.K.; Subbarao, P.M.V.
Abstract: Coal mills are bottleneck in coal–fired power generation process due to difficulty in developing efficient controls and faults occurring inside the mills. In this paper, a dynamic coal mill model is developed using conservation laws and empirical relations. The physical processes occurring inside the mill such as grinding, pneumatic transport, drying, heat transfer, and classification are modeled. Differential Evolution is used to estimate the model parameters. The model is validated using data obtained from a 500 MW plant in India. An application of the proposed model for online estimation of moisture in the raw coal is presented. Highlights: Dynamic coal mill model based on conservation laws and empirical relations. A model which can replicate the entire milling operation from startup to shutdown. Model with minimum number of parameters; suitable for real time applications. Validation using real time plant data, obtained over a period of one week. Application of the model for online estimation of moisture content in the raw coal using EKF.